Morphology and magnetic properties of cobalt and cobalt-platinum magnetic nanoparticles prepared using reverse microemulsion - Bahmanrokh, Ghazaleh (2012)
This thesis is focused on the preparation of cobalt and cobalt-platinum type magnetic nanoparticles by the reverse-micelle microemulsion method for the applications in ultra-high density magnetic recording media that could overcome the thermal stability limit of currently materials. Synthesizing nanoparticles (NPs) with a narrow size distribution and high uniformity is one of the prime goals of this research. To achieve that, nanoparticles were synthesized in aqueous cores of cetyltrimethylammonium bromide (CTAB) reverse micelles as a nano-reactor allowing nucleation and growth within a confined space and gaining the advantage of size restriction. A variation was introduced to the molar ratio of water to surfactant (ω) in preparing Co and CoPt3 nanoparticles for four different ω:5, 10, 15 and 20. The as-prepared Co and CoPt3 nanoparticles were annealed further under argon atmosphere at 400ᵒC and 800ᵒC respectively. Moreover since Co nanoparticles are rapidly oxidized upon exposure to air, coating of Co and CoPt3 nanoparticles with a gold shell was performed in the next step. Physical characteristics of as-prepared and annealed samples were studied as well. XRD patterns of as-synthesized samples show the evidence that highly crystalline CoPt3 NPs could form during precipitation in reverse-micelle microemulsion. However as-synthesized and annealed Co NPs showed very low crystallinity. Sintering of CoPt3 caused an improvement in the crystallinity and disordered-ordered phase transition at 800ᵒC, which subsequently changed the magnetic properties of CoPt3. Coercivity increased with an increase of the ω ratio or particle size for both Co and CoPt3 NPs. Annealing resulted in a significant increase in the coercivity which showed the highest values of 446.8Oe and 712.2Oe respectively for Co and CoPt3 at room temperature which makes them good candidates for recording media. The TEM and FESEM results showed nanoparticles with spherical shape and narrow size distribution. The average size was in good agreement with the crystal size calculated by the Scherer formula and increased with an increased ω ratio. Hysteresis loops at room temperature for the as-synthesized Co and CoPt3 show superparamgnetic-ferromagnetic behavior above the blocking temperature at 45K. Core-shell Co-Au, CoPt3-Au NPs were synthesised via a two step reduction process in reverse-micelle microemulsion solution. Gold coating increased the crystallinity of Co NPs but decreased that of CoPt3. TEM results in high magnification show a core-shell structure with shell thickness around 2-3nm. After gold coating of Co NPs the coercivity decreased whereas the saturation magnetization increased due to oxidation protection. A typical high blocking temperature around 50 K was observed for CoPt3-Au nanoparticles via a simple method.